A proposed cumulative record for the U.P. Elementary School - dela Cruz, Luz Samonte 1915- ([Quezon City University of the Philippines], 1954)
A cumulative record of information for the UP Elementary School is devised in this study to serve as a basis for a guidance program in the said school.
Bibliography: p. 85-88.
Thesis (M.Ed.)--University of the Philippines, 1954
Typewritten
Vita